2006
DOI: 10.1021/bc060180n
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Activation of Second-Generation Dendritic Prodrugs:  Conjugation of Self-Immolative Dendrimers with Poly(ethylene glycol) via Click Chemistry

Abstract: Single-triggered disassemble dendrimers were recently developed and introduced as a potential platform for a multi-prodrug. These unique structural dendrimers can release all of their tail units through a self-immolative chain fragmentation initiated by a single cleavage at the dendrimer's core. There are several examples for the bioactivation of first-generation self-immolative dendritic prodrugs. However, enzymatic activation failed for second-generation self-immolative dendrimers. The hydrophobic large mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 18 publications
0
102
0
1
Order By: Relevance
“…As an example of a dendrimer used for drug delivery, Gopin et al (70) reported the synthesis and evaluation of a single-triggered disassemble dendrimer as a potential platform for a multi-prodrug. "These unique structural dendrimers can release all of their tail units through a selfimmolative chain fragmentation that is initiated by a single cleavage at the dendrimer's core" (70).…”
Section: Other Polymer-related Applications Of Click Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a dendrimer used for drug delivery, Gopin et al (70) reported the synthesis and evaluation of a single-triggered disassemble dendrimer as a potential platform for a multi-prodrug. "These unique structural dendrimers can release all of their tail units through a selfimmolative chain fragmentation that is initiated by a single cleavage at the dendrimer's core" (70).…”
Section: Other Polymer-related Applications Of Click Chemistrymentioning
confidence: 99%
“…"These unique structural dendrimers can release all of their tail units through a selfimmolative chain fragmentation that is initiated by a single cleavage at the dendrimer's core" (70). To allow enzymatic activation of the second-generation of self-immolative dendrimers, azide-monoterminated PEG was conjugated to the dendritic platform via click chemistry, which prevented aggregate formation of the hydrophobic drugs.…”
Section: Other Polymer-related Applications Of Click Chemistrymentioning
confidence: 99%
“…However, if a highly versatile reaction, such as the CuAAc reaction, is utilized in combination with convergent growth, the risk of partial coupling of the active sites in the dendritic core is diminished. For example, Shabat et al 43 reports on the convergent attachment of PEG-chains to a dendritic core via Click chemistry using only stoichiometric amounts of the linear polymer.…”
Section: Hybrid Structuresmentioning
confidence: 99%
“…These results show that the incorporation of a specific enzyme substrate which would be cleaved by a protease overexpressed in tumor cells could be a suitable dendritic pro-drug system. 179 …”
Section: Drug Loading By Chemical Conjugationmentioning
confidence: 99%